2009
DOI: 10.1007/s00418-009-0621-1
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporter genes in the mammary gland of lactating cows

Abstract: This study is the first to examine the expression of the 14 monocarboxylate transporter genes (MCT1-MCT14) in the mammary gland of mammals. RT-PCR, Western blot, immunohistochemistry, and immunofluorescence confocal laser microscopy were applied in a comprehensive approach to assess the expression and cellular localization of MCTs in the mammary gland of lactating cattle. RT-PCR revealed the existence of nine MCT isoforms, namely MCT1, MCT2, MCT3, MCT4, MCT5, MCT8, MCT10, MCT13, and MCT14 in cow mammary gland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Kirat and Kato (76) have detected expressions of MCT1, MCT2, MCT4, and MCT8 by immunoblotting and RT-PCR in the mammary gland of cows; MCT1 and MCT2 have been described as localized at the basolateral membrane of alveolar epithelial cells with the expression of MCT4 at the apical side. Unfortunately, immunostaining of CD147 in cows failed to confirm the cellular localization of MCTs (76). Our in situ hybridization analysis in the murine mammary gland could not detect any significant mRNA expression of MCT2 or MCT4.…”
Section: The Skin Including Sebaceous Gland and Mammary Glandmentioning
confidence: 57%
“…Kirat and Kato (76) have detected expressions of MCT1, MCT2, MCT4, and MCT8 by immunoblotting and RT-PCR in the mammary gland of cows; MCT1 and MCT2 have been described as localized at the basolateral membrane of alveolar epithelial cells with the expression of MCT4 at the apical side. Unfortunately, immunostaining of CD147 in cows failed to confirm the cellular localization of MCTs (76). Our in situ hybridization analysis in the murine mammary gland could not detect any significant mRNA expression of MCT2 or MCT4.…”
Section: The Skin Including Sebaceous Gland and Mammary Glandmentioning
confidence: 57%
“…31 Nevertheless, some studies show that MCT4 can localize to the apical membranes in certain tissues. 32,33 Even in the same organ (e.g., small and large intestine), the expression profile of MCT4 varies depending on the region. 33 It has also been reported that MCT expression in a tissue can vary among different animal species.…”
Section: Discussionmentioning
confidence: 99%
“…As for MCT14, its substrate profile is still unknown and the expression data are limited. MCT14 has been found in bovine mammary gland, in the gastrointestinal tracts of cattle and the mammary glands of lactating cows [ 21 23 ], but there is no detailed immunohistochemical analysis of MCT14 expression in mouse brain.…”
Section: Introductionmentioning
confidence: 99%